Model Penggunaan Media Sosial yang Efektif Sesuai dengan Kaidah Ayat Surah Al-Ashr Khususnya bagi Para Pelajar - Imamul Arifin; Sherly Mei Yanti; Rahmadani Najwa Alfriza (Al-Ittishol: Jurnal Komunikasi dan Penyiaran Islam, 2022)
Research has been carried out on the Effective Use of Social Media Models in accordance with the Rules of the Qur'an for Students. Based on the main problem that often arises that social media users will spend time, especially among students. This research is intended for students or students with online research methods through survey pages. The aim of knowing the impact of using media and efforts to prevent the implementation of learning through social media in accordance with the creed of the Qur'an. The results showed that 53.8% of students used more than 4 hours, 23.1% used 3 to 5 hours and 1 to 3 hours. For the proportion of applications used for this period, the top three are WhatsApp with 92.3%, Instagram 76.9%, and Pinterest 38.5%. From the results of this study, it was concluded that the use of social media that is not guided by the surah of the Qur'an, namely Al-ashr will result in the learning process in the network becoming social media which results in wasted time.